The Impact of Risk Disclosure on the Influence of Leverage, Profitability on Company Value (E-Jurnal Akuntansi, 2026)
This study aims to analyze the effect of leverage and profitability on firm value with risk disclosure as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange during the post-COVID-19 economic recovery period from 2020 to 2024. The research sample was selected using purposive sampling based on the availability of complete financial statements and annual reports throughout the observation period and published on the Indonesia Stock Exchange website. Firm value is viewed as a reflection of market confidence in the company’s financing policies and financial performance, while risk disclosure is measured using the PSAK 60 disclosure index, which encompasses various types of financial and operational risks. Firm value is measured using Tobin’s Q, leverage is measured by the Debt to Equity Ratio (DER), profitability is measured by Return on Equity (ROE), and risk disclosure is measured using a disclosure index based on PSAK 60. Data analysis was conducted using Moderated Regression Analysis (MRA) on financial statements and annual reports of the purposively selected sample companies. The results indicate that leverage and profitability have a significant positive effect on firm value, and risk disclosure also has a direct, significant positive effect on firm value. These findings confirm that risk transparency serves as a positive signal for investors in evaluating energy sector companies characterized by high levels of risk. This also suggests that high-quality risk disclosure can become a corporate strategy for enhancing firm value.
Keywords: Leverage; Profitability; Risk Disclosure; Firm Value; Moderation; PSAK 60